Strategic aspects of countering corruption in Belarus: problems and ways of their solution - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2020)
The article discusses some problems of the anti-corruption strategy. It has been suggested that in order to counter this social phenomenon, it is necessary to develop a systemic strategy that covers all areas of the life of society and the state, the implementation of which will require a long time and the change of several generations of people. The main problems on the way to eliminating corruption, according to the author, are associated with the formation of a system of law and human potential. The author concludes that it is advisable to develop another normative definition of corruption, covering the entire spectrum of corruption manifestations that make up this social phenomenon and must be neutralised by applying active and passive measures of law enforcement. It is proposed to put into practice a system of preventive measures aimed at candidates applying for or becoming a public servant.